2015
DOI: 10.1111/cen.12869
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adipocytokines and traditional cardiometabolic risk factors in young male cancer survivors: an age‐matched control study

Abstract: A high leptin: adiponectin ratio, hypercholesterolaemia and low FAI are observed in young male cancer survivors, especially those who received radiotherapy involving the testes or were diagnosed at a later age. In view of their youth and known increased risk of cardiovascular death, treatment strategies are required to address this cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Young adult survivors of childhood malignancy have an 8-fold-greater risk of cardiac mortality than the healthy population [27], and cardiovascular morbidity is one of the commonest late effects seen in cancer survivors. Cancer survivors have an increase in all the risk factors for cardiovascular disease including obesity, dyslipidaemia, insulin resistance, and type 2 diabetes [28, 29]. The increased risk particularly affects people who have had higher-intensity treatments such as haematopoietic stem cell transplantation [30].…”
Section: Discussionmentioning
confidence: 99%
“…Young adult survivors of childhood malignancy have an 8-fold-greater risk of cardiac mortality than the healthy population [27], and cardiovascular morbidity is one of the commonest late effects seen in cancer survivors. Cancer survivors have an increase in all the risk factors for cardiovascular disease including obesity, dyslipidaemia, insulin resistance, and type 2 diabetes [28, 29]. The increased risk particularly affects people who have had higher-intensity treatments such as haematopoietic stem cell transplantation [30].…”
Section: Discussionmentioning
confidence: 99%
“… 50 , 51 In cancer survivors, who are known to have increased risk of CVD, excess rates of obesity and metabolic disorders have been observed which are thought to be the consequence of late effects of chemotherapy and radiotherapy. 52 Low birthweight, a marker of poor early growth, is strikingly associated with metabolic disorders in adult life. Using the thrifty and programming hypotheses, Barker suggested that poor nutrition in utero and early life has an adverse effect on the structure and function of vital organs.…”
Section: Pathophysiologymentioning
confidence: 99%
“… 72 In individuals with type 2 diabetes whose risk for CVD is accentuated, more intensive risk factor management is warranted. In the case of cardiometabolic risk-associated drug therapy for conditions such as congenital adrenal hyperplasia 50 , 51 and cancer, 52 increased monitoring and early interventions are required to limit the long-term adverse effects of the treatment.…”
Section: Medical Managementmentioning
confidence: 99%
“…[3][4][5][6][7][8] Causes of CV disease among cancer survivors include the effects of chemotherapy and other anticancer agents, as well as that of radiation. 9,10 Insulin resistance 11,12 and higher C-reactive protein levels 13 are associated with certain cancer treatments. The relatively high prevalence of obesity and physical inactivity during the cancer survivorship period add to the risk of developing CV disease.…”
Section: Background and Significancementioning
confidence: 99%